Leadership and motivation as key drivers of teacher performance: A quantitative study at SMA Negeri 1 Mendoyo - Diantara, I Putu Indra Artha; Yudana, I Made; Sulindawati, Ni Luh Gede Erni (Asatiza: Jurnal Pendidikan, 2025)
This study investigates the individual and simultaneous contributions of (1) situational leadership, (2) work motivation, (3) work ethic, and (4) job satisfaction to teacher performance at SMA Negeri 1 Mendoyo, Jembrana Regency. Employing an ex post facto design, the research encompassed the entire population of 42 teachers, making it a population study. Data were collected using Likert-scale questionnaires and analyzed through product-moment correlation, partial correlation, and multiple regression. The results demonstrated significant individual contributions: situational leadership accounted for 81.5% (R² = 0.815, p < 0.01, effective contribution = 22.48%), work motivation for 89.6% (R² = 0.896, p < 0.01, effective contribution = 32.53%), work ethic for 77.2% (R² = 0.772, p < 0.01, effective contribution = 22.33%), and job satisfaction for 76.3% (R² = 0.763, p < 0.01, effective contribution = 16.76%). Collectively, these factors explained 94.1% of the variance in teacher performance. These findings underscore the synergistic role of leadership, motivation, and ethics in enhancing teacher performance, offering actionable insights for school administrators.